Mengembangkan Kemampuan Siswa SMK dalam Mengembangkan Web - Saragih, Saut Pintubipar; Darmansah, Darmansah; Arnomo , Sasa Ani; Svinarky, Irene (ASOSIASI IDEBAHASA KEPRI, 2024)
Nowadays it is such a crucial element to provide training for students before entering th job market after school. Taking an Exam for Profesional certification is one of available option they can obtain. This program was conducted to optimize the students' preparation for the certification assessment. This crucial acquisition of competency certification nowadays represents a significant advantage for students about to complete their education, whether at the university level or in secondary schools. One such in-demand competency certification for IT vocation school is junior web development certification. Web development skills are increasingly essential in today's digital economy, providing students with the tools to create and manage web-based applications and services. Early exposure to web development can enhance students' problem-solving abilities and technical proficiency, preparing them for diverse career opportunities in the technology sector. Recognizing the importance and benefits of this certification, it is deemed necessary to conduct training on this competency as part of a community service program. The result of this program is to enhance the ability of students to maintain their understanding of the web development fundamentals and their ability to follow correct and proper development methods